Accuracy of Response Assessment Positron Emission Tomography-Computed Tomography Following Definitive Radiotherapy Without Chemotherapy for Head and Neck Squamous Cell Carcinoma. Issue 4 (April 2019) - Arunsingh, M.; Vaidyanathan, S.; Dyker, K.E.; Sen, M.; Scarsbrook, A.F.; Prestwich, R.J.D.
Abstract: Aim: There are few data to inform on the use of response assessment 2-[fluorine-18]-fluoro-2-deoxy-d -glucose (FDG) positron emission tomography-computed tomography (PET-CT) following radical radiotherapy without chemotherapy for head and neck squamous cell carcinoma (HNSCC). This retrospective study evaluated the accuracy of PET-CT in HNSCC following radical radiotherapy. Materials and methods: In total, 138 patients with HNSCC treated with radical radiotherapy without chemotherapy who underwent a baseline and response assessment FDG PET-CT were identified. FDG PET-CT outcomes were analysed with reference to clinicopathological outcomes. Results: The median follow-up was 26 months. FDG-avid disease at baseline was present for the primary site and lymph nodes in 118 and 86 patients, respectively. With regard to the primary tumour, the negative predictive value (NPV) of a complete metabolic response (CMR) was 95%; the positive predictive value (PPV) of equivocal uptake and a positive scan were 6% and 82%, respectively. The likelihood ratios for a CMR, equivocal and positive scans of the primary site were 0.19, 0.22, 14.8, respectively. With regard to lymph node disease, the NPV of a CMR was 91%, the PPV of equivocal uptake and a positive scan were 33% and 88%, respectively. Likelihood ratios for lymph node disease for CMR, equivocal and positive scans were 0.19, 0.97 and 15.1, respectively. Conclusion: Compared with the accuracy reported in the literature following chemoradiotherapy, response assessment FDG PET-CT following radical radiotherapy without chemotherapy had a similarly high NPV, whereas the PPV following a positive scan was higher. Highlights: Few data are available on the accuracy of PET-CT response assessment after radiotherapy alone. PET-CT had a high negative predictive value for primary and lymph node disease. Positive predictive value was low for equivocal scans but high for positive scans. Overall accuracy of PET-CT is similar to that reported following chemoradiotherapy.